2019
DOI: 10.1136/jim-2018-000858
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic status and risk of hospitalization due to child maltreatment in the USA

Abstract: Child maltreatment remains a significant problem in the USA. There is a dearth of literature examining the association of socioeconomic status (SES) and incidence of child maltreatment among hospitalized children across the entire USA. Our aim was to study the association between SES and incidence and mortality from child maltreatment among hospitalized children in the USA. We used 2013–2014 data from the Nationwide Inpatient Sample, a discharge database representative of all hospitals in the USA. Internationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The various types of childhood adversities examined in the literature tend to co-occur, with stress-exposed youth rarely experiencing only one type of stressor (Smith & Pollak, 2020). For instance, maltreatment and peer victimization are more prevalent among socioeconomically disadvantaged families (Imran et al, 2019; Kim & Drake, 2018; Tippett & Wolke, 2014). Maltreated youth are also more likely to be bullied compared to their nonmaltreated peers (Shields & Cicchetti, 2001).…”
Section: Childhood Stress and Inflammationmentioning
confidence: 99%
“…The various types of childhood adversities examined in the literature tend to co-occur, with stress-exposed youth rarely experiencing only one type of stressor (Smith & Pollak, 2020). For instance, maltreatment and peer victimization are more prevalent among socioeconomically disadvantaged families (Imran et al, 2019; Kim & Drake, 2018; Tippett & Wolke, 2014). Maltreated youth are also more likely to be bullied compared to their nonmaltreated peers (Shields & Cicchetti, 2001).…”
Section: Childhood Stress and Inflammationmentioning
confidence: 99%
“…A systematic review of social determinants of child maltreatment identified significant and robust links between poverty and several other socioeconomic status indicators (e.g., parental educational attainment, housing instability, food insecurity, and insurance) with heightened rates of maltreatment (Hunter & Flores, 2021). For example, youth from lower socioeconomic status households experience greater rates of maltreatment as well as more negative outcomes (Imran et al, 2019), and children living below the family poverty level experience significantly more adverse childhood experiences (Goldstein et al, 2021). Similarly, autistic youth are more likely to experience income insufficiency (Berg et al, 2016), and autistic youth from lower income households are at disproportionate risk for adverse childhood experiences (Kerns et al, 2017).…”
Section: Associations With Incomementioning
confidence: 99%
“…It should be noted that other stressors that also affect neurocognitive development, such as childhood maltreatment, may be important to consider as potential covariates of SES. While not a component of SES, maltreatment (i.e., abuse and neglect) is sometimes correlated with childhood SES . However, recent evidence has shown that they independently influence limbic volumes measured in young adults, and brain volume, cerebral blood flow, and cognitive functioning in children and young adults …”
Section: Socioeconomic Statusmentioning
confidence: 99%
“…While not a component of SES, maltreatment (i.e., abuse and neglect) is sometimes correlated with childhood SES. 27 However, recent evidence has shown that they independently influence limbic volumes measured in young adults, 28 and brain volume, cerebral blood flow, and cognitive functioning in children and young adults. 29 Thus, it is important that researchers consider multiple SES components within a study to separate their respective contributions to research outcomes.…”
Section: Socioeconomic Statusmentioning
confidence: 99%